2005
DOI: 10.1614/ws-04-050r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating plant resources to enhance beneficial arthropods in agricultural landscapes

Abstract: Annual crop fields typically are simple habitats dominated by a few plant species where pesticides play a major role in managing weed and insect infestations. Recently, there has been significant interest in the potential to reduce reliance on pesticides by manipulating plant species and communities to benefit natural enemies of insects and weeds. Such efforts aim to enhance natural enemy impact by providing appropriate food, shelter, and hosts, and efforts typically are accomplished by manipulation of plant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
17

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(139 citation statements)
references
References 61 publications
3
119
0
17
Order By: Relevance
“…In monocultures, increased herbivory could be due to how concentrated the food source is, making it easier to find host plants; higher pest tenure time; higher herbivore feeding and reproductive rates; or changes in crop quality (Andow 1991b). In addition, the lack of plant diversity decreases the diversity and abundance of predator and parasitoid natural enemies of crop pests (Hooks & Johnson 2003;Landis et al 2005;Lavandero et al 2006). In the widely studied insect communities of cruciferous crops, research has shown that when planted as mixtures rather than sole crops, herbivore responses include reduced colonization, reduced adult tenure time in the marketable crop, and oviposition interference ( Hooks & Johnson 2003).…”
Section: Ecological Management Of Arthropod Pestsmentioning
confidence: 99%
See 1 more Smart Citation
“…In monocultures, increased herbivory could be due to how concentrated the food source is, making it easier to find host plants; higher pest tenure time; higher herbivore feeding and reproductive rates; or changes in crop quality (Andow 1991b). In addition, the lack of plant diversity decreases the diversity and abundance of predator and parasitoid natural enemies of crop pests (Hooks & Johnson 2003;Landis et al 2005;Lavandero et al 2006). In the widely studied insect communities of cruciferous crops, research has shown that when planted as mixtures rather than sole crops, herbivore responses include reduced colonization, reduced adult tenure time in the marketable crop, and oviposition interference ( Hooks & Johnson 2003).…”
Section: Ecological Management Of Arthropod Pestsmentioning
confidence: 99%
“…Habitat management involves vegetation diversification at multiple scales (Landis et al 2005). Use of insectary plantings or leaving strips of unharvested plants are examples of in-field strategies, whereas wildflower borders, grassy buffer strips, windbreaks and hedgerows are examples of field margin diversification techniques.…”
Section: Conservation Biological Controlmentioning
confidence: 99%
“…Timbulnya masalah ledakan hama di sebuah wilayah kemungkinan disebabkan oleh model pertanian monokultur seperti dinyatakan oleh Andow (1991) dan Mensah, (1999). Oleh karena itu, alternatif strategi budidaya yang berbasis keragaman hayati tinggi kemudian banyak diusulkan oleh para ahli, misalnya melalui penyediaan ekosistem yang ramah pada musuh alami hama (Andow, 1991;Landis et al, 2005).…”
Section: Pengantarunclassified
“…Landis et al (2005) menyebutkan bahwa banyak tanaman dan tumbuhan merupakan sumber pakan langsung bagi organisme musuh alami, misalnya dengan menyediakan nektar dan polen, dan secara tidak langsung menyediakan mangsa dan inang, di samping mengelola iklim mikro yang sesuai dengan kebutuhan hidup musuh alami.…”
Section: Sistem Pertanian Berbasis Konservasi Musuh Alamiunclassified
“…Spiders tend to be more numerous in agroecosystems where surface residue cover is diversified by planting intercrops and cover crops, retaining weeds or conserving crop residues (Sunderland and Samu 2000;Landis et al 2005). Yet, there was no difference in the mean number of Araneae and Opiliones collected in the CT and NT plots ( Table 3), suggesting that the microenvironment of cultivated soils was also favorable for spiders and harvestmen.…”
Section: Insect Populationsmentioning
confidence: 99%